Imprint of a dissolved cobalt basaltic source on the Kerguelen Plateau - Bown, J; Boye, M; Laan, P; Bowie, AR; Park, Y-H; Jeandel, C; Nelson, DM (Biogeosciences, 2012)
Processes of cobalt (Co) entrainment from shelfsediments over the Kerguelen Plateau were studied duringthe KEOPS (Kerguelen Ocean Plateau compared Study) inorder to explain the exceptionally high dissolved cobalt concentrationsthat have been measured in the surface watersabove the Kerguelen Plateau, and in intermediate and deepwaters above its eastern slope. Lateral advection and dissolutionof Co contained in basalt sediments around Heard Island,a main source of lithogenic Co in the study area, wereshown to imprint the process of surface enrichment over theplateau. Dissolved Co enrichment was strongest at the interceptof the eastern slope with intermediate and deep waters,probably due to more efficient mobilisation of the sedimentsin the slope current, in addition to advection of Co-enrichedand low-oxygenated ocean water masses. In surface waters, the strong sedimentary Co inputs wereestimated to be much higher than biological Co uptake inphytoplankton blooms, underlining the potential use of dissolvedcobalt as tracer of the natural iron fertilization abovethe Kerguelen Plateau. Based on a simple steady-state balanceequation of the external input of dissolved iron overthe plateau, the fertilization of iron inferred by using dissolvedCo as a tracer of basalt sources is estimated to be28 10 2 21 10 2 t yr −1 in surface waters of the KerguelenPlateau. This estimate is consistent with preceding ones(Zhang et al., 2008; Chever et al., 2010), and the calculatediron supply matches with the phytoplankton demand(Sarthou et al., 2008).